2019
DOI: 10.1016/j.apcatb.2018.12.062
|View full text |Cite
|
Sign up to set email alerts
|

On the real catalytically active species for CO2 fixation into cyclic carbonates under near ambient conditions: Dissociation equilibrium of [BMIm][Fe(NO)2Cl2] dependant on reaction temperature

Abstract: An imidazolium based iron-containing ionic liquid [BMIm][Fe(NO)2Cl2] (BMIm = 1n-butyl-3-methyl-imidazolium) has been synthesized for the first time and fully characterized employing a wide range of techniques. The iron-based containing ionic liquid was found to be an active catalyst for the cycloaddition of CO2 to epoxides, giving high conversions for various substrates under near ambient conditions. In addition, the catalytic system showed a good recycling performance for five consecutive reaction cycles. Key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 122 publications
1
30
0
Order By: Relevance
“…Moreover, in various cases, the interaction of the IL pair changes the reactivity of the trapped water, which can easily react with substrates, products, and even with the IL. [8,9,19,[27][28][29][30] In this contribution, the different modes of interaction of CO 2 with bare ILs containing both nonbasic and mainly basic anions will be presented and discussed critically, considering recent examples reported in the literature. Finally, it will be demonstrated that simple concepts of acid-base chemistry can be used to explain and to design new ionic fluids for CO capture and activation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in various cases, the interaction of the IL pair changes the reactivity of the trapped water, which can easily react with substrates, products, and even with the IL. [8,9,19,[27][28][29][30] In this contribution, the different modes of interaction of CO 2 with bare ILs containing both nonbasic and mainly basic anions will be presented and discussed critically, considering recent examples reported in the literature. Finally, it will be demonstrated that simple concepts of acid-base chemistry can be used to explain and to design new ionic fluids for CO capture and activation.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, these materials exhibit unusual anisotropic thermal expansion processes, which can be related to the ability of the organic moiety to present translational and reorientational phenomena that govern properties such as magnetism and solid-state ionic conduction. Moreover, from a technological point of view, due to their very interesting features in terms of Lewis-acidity, they are recently being applied as catalysts in reactions such as glycosidation, 18,19 Michael addition, 20 desulfurization 21 and CO 2 xation into cyclic carbonates, 22 among others.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive epoxide such as (+ /À )-epichlorohydrin 3 b, due to electronegative effect of its substituent that facilitated the nucleophilic attack to open the epoxide ring, [27] gave quantitative yield of cyclic carbonate (entry 2, Table 3). On the other hand, the low solubility of complex 2 b in alkyl epoxides even at high temperatures caused a drop in the reaction yield, whose effect is more pronounced on increasing chain length, as exemplified by the difference between propylene oxide and 1,2-hexene oxide (compare entry 3 with entry 7 in Table 3).…”
Section: Resultsmentioning
confidence: 99%